Credit growth in the Middle East, North Africa, and Central Asia region - Crowley, Joe (IMF working paper, 2008)
Rapid private sector credit growth in the Middle East, North Africa, and Central Asia has been a result of strong economic growth, financial deepening, and banks' willingness to explore consumer credit markets. Economic growth, the initial ratio of private sector credit to GDP, price volatility, and nonoil exports are found to be significant explanatory variables, while oil exports and spillovers from oil exporting neighbors were not found to have any significance. The credit growth has financed consumer spending and home ownership rather than investment.